Transepithelial transport across Caco-2 cell monolayers of angiotensin converting enzyme (ACE) inhibitory peptides derived from simulated in vitro gastrointestinal digestion of cooked chicken muscles. (15th June 2018) - Sangsawad, Papungkorn; Roytrakul, Sittiruk; Choowongkomon, Kiattawee; Kitts, David D.; Chen, Xiu-Min; Meng, Guangtao; Li-Chan, Eunice C.Y.; Yongsawatdigul, Jirawat
Highlights: Breast digests were showed higher ACE inhibitory activity than thighs. The 1-kDa permeate of digests revealed the highest ACE inhibitory activity. Mild thermal treatment resulted higher transported peptides and ACE inhibition. Potency of ACE inhibition depends on permeability of peptide. Nine transported peptides were tripeptides, APP showed the highest ACE inhibition. Abstract: Korat-chicken breast and thigh were subjected to heating at 70, 100 or 121 °C for 30 min and simulated in vitro gastrointestinal digestion. At 70 or 100 °C heating, digests of breast possessed higher ACE inhibitory activity than those of thigh. The highest ACE inhibitory activity was found in the digest of breast cooked at 70 °C (B/H-70), whereas breast heated at 121 °C (B/H-121) exhibited the lowest. The 1-kDa permeate of the B/H-70 digest revealed higher permeability through colorectal adenocarcinoma monolayers and ACE inhibitory activity than did B/H-121. Among nine transported peptides, APP derived from myosin showed the highest ACE inhibition, with a non-competitive characteristic (Ki 0.93 μM). Molecular docking showed that APP interacts with ACE via hydrogen bonds, electrostatic and van der Waals interactions. In conclusion, mild thermal treatment of chicken breast resulted in a higher amount of transported peptides, exerting higher ACE inhibitory activity, which could lead to potential health benefits.